Porcine Epidemic Diarrhea Virus Envelope Protein Blocks SLA-DR Expression in Barrow-Derived Dendritic Cells by Inhibiting Promoters Activation - Jie Wang (Frontiers Media S.A., 2021)
Porcine epidemic diarrhea (PED) is an acute, highly contagious intestinal swine disease caused by porcine epidemic diarrhea virus (PEDV). In addition to known PEDV infection targets (villous small intestinal epithelial cells), recent reports suggest that dendritic cells (DCs) may also be targeted by PEDV in vivo. Thus, in this study we used bone marrow-derived dendritic cells (BM-DCs) as an in vitro model of antigen-presenting cells (APCs). Our results revealed that PEDV replicated in BM-DCs and that PEDV infection of cells inhibited expression of swine leukocyte antigen II DR (SLA-DR), a key MHC-II molecule involved in antigen presentation and initiation of CD4+ T cell activation. Notably, SLA-DR inhibition in BM-DCs did not require PEDV replication, suggesting that PEDV structural proteins participated in SLA-DR transcriptional inhibition. Moreover, reporter assay-based screening indicated that PEDV envelope protein blocked activation of SLA-DRα and β promoters, as did PEDV-ORF3 protein when present during PEDV replication. Meanwhile, treatment of PEDV-infected BM-DCs with MG132, a ubiquitin-proteasome degradation pathway inhibitor, did not restore SLA-DR protein levels. Additionally, PEDV infection of BM-DCs did not alter SLA-DR ubiquitination status, suggesting that PEDV infection did not affect SLA-DR degradation. Furthermore, additions of PEDV structural proteins to HEK-293T-SLA-DR stably transfected cells had no effect on SLA-DR protein levels, indicating that PEDV-mediated inhibition of SLA-DR expression acted mainly at the transcriptional level, not at the protein level. These results provide novel insights into PEDV pathogenic mechanisms and viral-host interactions.